2012
DOI: 10.3892/ijo.2012.1525
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ADAMTS-1, ADAMTS-4, ADAMTS-5 and TIMP3 by hepatocellular carcinoma cell lines

Abstract: Abstract.Little is known about the expression or role of ADAMTS-1, -4 and -5 and their endogenous inhibitor TIMP3 in the liver in physiological and pathological conditions. Their expression was, therefore, investigated in the hepatocellular carcinoma cell lines HepG2 and HuH-7 using qRT-PCR and western blotting, and their cellular localisation by immunocytochemistry. Cytokine treatments were used to assess mRNA and protein modulation. ADAMTS-1, -4, -5 and TIMP3 mRNA and protein were detected in both HepG2 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Furthermore, IHC analysis of an HCC TMA similarly showed a reduced cytoplasmic expression of TIMP-3 protein in cancer cells relative to normal non-cancerous cells. These results are similar to the studies that indicated that the expression of TIMP-3 was inhibited in malignant cancers [16], [18], [20], [38]. Moreover, positive TIMP-3 expression in HCC was negatively correlated with certain clinical pathologic items, including portal vein invasion and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, IHC analysis of an HCC TMA similarly showed a reduced cytoplasmic expression of TIMP-3 protein in cancer cells relative to normal non-cancerous cells. These results are similar to the studies that indicated that the expression of TIMP-3 was inhibited in malignant cancers [16], [18], [20], [38]. Moreover, positive TIMP-3 expression in HCC was negatively correlated with certain clinical pathologic items, including portal vein invasion and lymph node metastasis.…”
Section: Discussionsupporting
confidence: 89%
“…TIMP-3 was localized in tumor cell cytoplasm, as previously described for renal, pancreatic, and esophageal tumors [22]. Despite its known inhibitory protease activity, increased TIMP-3 expression was associated with head-and-neck tumor development and progression [60].…”
Section: Discussionmentioning
confidence: 99%
“…Hyalectans have the ability to bind HA through their N-terminal globular domain (G1); the central domain carries most of the GAG chains and exhibits lectin-like activity located in the C-terminal globular domain (G3) [13,19]. The endogenous tissue inhibitor of metalloproteinase 3 (TIMP-3) regulates ADAMTS-1, -4, and -5 proteolytic activity [20,21,22]. …”
Section: Introductionmentioning
confidence: 99%
“…We previously observed expression of several ADAMTS members in murine adipose tissue and found a marked upregulation of ADAMTS5 during the development of obesity . Furthermore, ADAMTS5 is expressed by hepatocellular carcinoma cell lines . ADAMTS5 is the most prominent enzyme in aggrecan degradation , although it also degrades other substratres including versican, biglycan, decorin and collagen .…”
mentioning
confidence: 98%